1970
DOI: 10.3329/jbt.v5i2.9984
|View full text |Cite
|
Sign up to set email alerts
|

Employee Participation in Decision Making in RMG sector of Bangladesh: Correlation with Motivation and Performance

Abstract: Participation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 5 publications
(1 reference statement)
2
19
0
1
Order By: Relevance
“…Consistent with PDM and MEOC literature clear support for these relationships was found and both PDM and MEOC were found to be correlated and significantly explained variation in CTY. It was argued that employee's participation in decision making will effect employee's creativity as participative decision making affects the performance, organization commitment, turnover, motivation and satisfaction of the employees, productivity [12] [13] [17]- [20] [25] and performance, organization commitment, turnover and satisfaction of the employees has significant relationship with creativity [14] [15] [21] [23]. A significant and positive relationship was found between PDM and CTY.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with PDM and MEOC literature clear support for these relationships was found and both PDM and MEOC were found to be correlated and significantly explained variation in CTY. It was argued that employee's participation in decision making will effect employee's creativity as participative decision making affects the performance, organization commitment, turnover, motivation and satisfaction of the employees, productivity [12] [13] [17]- [20] [25] and performance, organization commitment, turnover and satisfaction of the employees has significant relationship with creativity [14] [15] [21] [23]. A significant and positive relationship was found between PDM and CTY.…”
Section: Discussionmentioning
confidence: 99%
“…A significant and positive impact of job satisfaction exists on employee's creativity [23] and significant strong positive relation exist between participation is decision making and job satisfaction [4]. There is a significant relationship between employee involvement in decision making and firm's performance [14] [20]. Participation in decision making results in satisfaction of employees and increase in productivity and profit [14].…”
Section: Employee's Participation In Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that participative management approach is one of the ways to enhance productivity (Tchapchet et al, 2014;Conte, & Svejnar, 1988). Employee participation in decision-making enhances motivation, job performance, and organisational growth (see Gollan, & Wilkinson, 2007;Kim et al, 2010;Bhuiyan, 2010). On the other hand, some studies have conflicting views on whether or not an increase in employee participation directly affects organisational performance.…”
Section: Participatory Decision-making and Firm Performancementioning
confidence: 99%
“…al, 2015;Irawanto, 2015). The opportunity for increased job involvement provided by participative techniques addresses the growing desire among workers to take part in decision making affecting their jobs and to be active contributors to the system rather than merely job holders (Bhuiyan, 2010)..…”
Section: Introductionmentioning
confidence: 99%